2007
DOI: 10.1111/j.1475-097x.2007.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of acute myocardial infarction using the 12‐lead ECG plus inverted leads versus the 16‐lead ECG (with additional posterior and right‐sided chest electrodes)

Abstract: SUMMARYBackground: The electrocardiographic (ECG) diagnosis of acute myocardial infarction (MI) should be improved. This might be done either by regarding all 24 aspects (both positive and negative leads), or a subset hereof (for example 19-lead ECG), of the conventional 12-lead ECG or by using additional electrodes. The purpose of the study was to investigate the accuracy of the different ECG methods in diagnosing acute ST-elevation MI.Methods: The study population consisted of 479 patients admitted to Lund U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The detection of ST deviations in patient electrocardiograms is an essential method for the diagnosis of myocardial ischemia. Both clinical studies [ 1 6 ] and simulations [ 7 , 8 ] have shown that some forms of ischemia are visible neither in the standard ECG (see Table 1 ; sensitivity varies between 45% and 73% for detection of ST segment elevation) nor in body surface potential maps (BSPMs) [ 2 , 4 6 ]. Such “electrically silent” ischemia results in non-ST elevation myocardial infarction (NSTEMI).…”
Section: Introductionmentioning
confidence: 99%
“…The detection of ST deviations in patient electrocardiograms is an essential method for the diagnosis of myocardial ischemia. Both clinical studies [ 1 6 ] and simulations [ 7 , 8 ] have shown that some forms of ischemia are visible neither in the standard ECG (see Table 1 ; sensitivity varies between 45% and 73% for detection of ST segment elevation) nor in body surface potential maps (BSPMs) [ 2 , 4 6 ]. Such “electrically silent” ischemia results in non-ST elevation myocardial infarction (NSTEMI).…”
Section: Introductionmentioning
confidence: 99%
“…The use of cardiac serum markers as a supplement to the ECG has become standard in the assessment and risk stratification of acute myocardial ischemic injury 1216. In fact, serum troponin evaluation has recently become a gold standard for the diagnosis of myocardial necrosis 17–20.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] The use of cardiac serum markers as a supplement to the ECG has become standard in the assessment and risk stratification of acute myocardial ischemic injury. [12][13][14][15][16] In fact, serum troponin evaluation has recently become a gold standard for the diagnosis of myocardial necrosis. [17][18][19][20] However, serum troponin results are generally not immediately available, such that the emergency physician (EP) must implement AMI treatment protocols by relying only on the initial patient evaluation and associated 12-lead ECG interpretation.…”
mentioning
confidence: 99%
“…The sensitivity of manual interpretation for MI detection using a 12-lead ECG is only from 61 to 74% with the speci city ranging from 72 to 89.0%. [32][33][34][35] In contrast to previously prehospital computer algorithm interpretation for STEMI with the sensitivity of approximately 69%. [36][37][38] Our DLM provides extraordinary performance, which supports decision-making systems in clinical practice.…”
Section: Discussionmentioning
confidence: 85%